2010
DOI: 10.1101/gr.115956.110
|View full text |Cite
|
Sign up to set email alerts
|

Alu repeat discovery and characterization within human genomes

Abstract: Human genomes are now being rapidly sequenced, but not all forms of genetic variation are routinely characterized. In this study, we focus on Alu retrotransposition events and seek to characterize differences in the pattern of mobile insertion between individuals based on the analysis of eight human genomes sequenced using next-generation sequencing. Applying a rapid read-pair analysis algorithm, we discover 4342 Alu insertions not found in the human reference genome and show that 98% of a selected subset (63/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
114
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(123 citation statements)
references
References 43 publications
8
114
1
Order By: Relevance
“…TIP-chip (23) was used to map insertions (SI Materials and Methods). Previously reported polymorphic Alu elements were collected (10,11,21,22,(24)(25)(26)(27). The LD block for each GWAS signal (P ≤ 10 −8 ) was defined by proxy SNPs to the TAS (r 2 > 0.8) (SI Materials and Methods).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…TIP-chip (23) was used to map insertions (SI Materials and Methods). Previously reported polymorphic Alu elements were collected (10,11,21,22,(24)(25)(26)(27). The LD block for each GWAS signal (P ≤ 10 −8 ) was defined by proxy SNPs to the TAS (r 2 > 0.8) (SI Materials and Methods).…”
Section: Methodsmentioning
confidence: 99%
“…Due to the pace of these discovery efforts, no comprehensive list of all reported polymorphisms has been developed for Alu variants. Therefore, we collated reports of previously identified polymorphic Alu elements (10,11,21,22,(24)(25)(26)(27) to generate a catalog of 13,572 Alu variants distributed throughout the genome. These reports underscore that Alu polymorphisms are a major source of genetic diversity in humans.…”
Section: Significancementioning
confidence: 99%
“…[1][2][3] Genomic hypomethylation mainly affects repetitive transposable DNA elements, which comprise 45% of the human genome 4 ; these elements reside mainly in the intergenic and intronic regions of the genome and in noncoding and coding exons of the genome to a much lesser extent. 5 Long interspersed nucleotide element-1 (LINE-1) and ALU are major constituents of interspersed DNA repeats, constituting $17% and 11% of the human genome, respectively. 4 CpG sites located within LINE-1 and ALU are usually methylated in normal somatic tissues, a mechanism that is believed to have evolved as a major defense mechanism to repress these transposable genetic elements.…”
mentioning
confidence: 99%
“…In total, these trans retrotransposition events account for at least an additional 10% of human DNA (1). Moreover, several recent studies have further demonstrated that L1-mediated retrotransposition events are responsible for a significant proportion of interindividual genetic variation in the human population (33)(34)(35)(36)(37)(38)(39) and may cause intraindividual variation in the mammalian nervous system (40,41). L1 retrotransposition likely occurs by a mechanism termed target-site primed reverse transcription (TPRT) (42).…”
mentioning
confidence: 99%